Analysis and Research of Vibration Characteristic of Automobile Transmission - Zhang Jiping; Wu Wenxuan; Ma Weijin; Wang Junyuan (Jixie chuandong)
As an important part of automobile,the vibration characteristics of automobile transmission have important influence on the performance of the automobile. By studying and analyzing the vibration characteristics of an automobile transmission,the response of different position in different directions of the automobile transmission shell can be obtained. Through the analysis,the dynamic response of the automobile transmission is initial determined,the optimal excitation direction,natural frequency and frequency band of the automobile transmission are obtained. Through the experimental analysis,these parameters are obtained,the inherent characteristics of the automobile transmission is known,the foundation for the next step to analyze and optimize the structural optimization of the automobile transmission is provided.